Detailed numerical simulation of cathode spots in high-current vacuum arcs - Kaufmann, H. T. C. (2022)
A detailed numerical model of cathode spots in high-current vacuum arcs is given. The model provides a complete description of all phases of life of an individual spot taking into account the presence of metal vapor left over from a previous explosion, the interaction of the vaporized plasma from the cathode spot with the cathode surface, and Joule heat generation in the cathode body. Melting and motion of molten metal due to Lorentz force are also accounted for, together with surface tension effects and the pressure exerted by the plasma over the cathode surface. First results are presented and analyzed for copper cathodes with a protrusion and planar cathodes. Emphasis is given to the investigation of the effect of the vaporized plasma and of hydrodynamic processes. No thermal runaway is observed.